The utility of diffusion‐weighted whole‐body imaging with background body signal suppression in detecting metastatic lesion of germ cell carcinoma. Issue 5 (16th June 2021) - Yoshitomi, Kasumi Kaneko; Numao, Noboru; Umino, Yosuke; Fujiwara, Motohiro; Fujiwara, Ryo; Oguchi, Tomohiko; Komai, Yoshinobu; Yuasa, Takeshi; Yamamoto, Shinya; Yonese, Junji
Abstract : Introduction: Although the utility of diffusion‐weighted whole‐body imaging with background body signal suppression for assessing lymph node involvement or distant metastasis is renowned in many cancers, only few studies have revealed its utility for germ cell carcinoma. Some metastatic lesions of germ cell carcinomas are difficult to detect by conventional imaging. Case presentation: We report a case of a 70‐year‐old man with relapsed retroperitoneal germ cell tumor. Although his human chorionic gonadotropin levels increased, conventional imaging analysis showed no evidence of recurrence. Diffusion‐weighted whole‐body imaging with background body signal suppression was performed to search the metastatic lesion and detected metastatic sacral lesions. The patient responded well to local radiotherapy added to the steroid pulse and salvage chemotherapy and achieved long‐term recurrence‐free survival. Conclusion: Diffusion‐weighted whole‐body imaging with background body signal suppression has the potential to detect metastatic lesions not usually detected by conventional imaging methods.